Microhabitat diversity of ancient trees in Hyrcanian Old-Growth Forests, Iran - ZAHRA VEYSI; MOHSEN JAVANMIRI POUR; VAHID ETEMAD (Society for Indonesian Biodiversity, 2025)
Abstract. Veysi Z, Pour MJ, Etemad V. 2025. Microhabitat diversity of ancient trees in Hyrcanian Old-Growth Forests, Iran. Biodiversitas 26: 6523-6540. Old-growth forests play a critical role in maintaining biodiversity by supporting diverse Tree-related Microhabitats (TreMs), yet their distribution patterns in Iran’s Hyrcanian Old-Growth Forests remain understudied. This study presents the first systematic assessment of TreMs in temperate old-growth forests of northern Iran, focusing on 60 ancient trees across four key species: Oriental beech (Fagus orientalis), velvet maple (Acer velutinum), alder (Alnus subcordata), and hornbeam (Carpinus betulus) in Kheyrud Forest. We identified and analyzed 12 distinct TreM types, including cavities, deadwood, and epiphytes, and evaluated their spatial distribution using GIS alongside environmental variables (elevation, slope, stand structure). Our results demonstrate that velvet maple and beech trees host the highest TreM richness, functioning as keystone structures for habitat heterogeneity. Notably, velvet maple (A. velutinum) showed strong associations with woodpecker cavities, reflecting species-specific microhabitat relationships. Statistical analyses revealed significant variation in TreM distribution across tree species and forest types, emphasizing the importance of preserving diverse tree assemblages to sustain microhabitat complexity. These findings provide actionable insights for conserving the Hyrcanian Old-Growth Forests, a UNESCO-listed biodiversity hotspot, and highlight the global relevance of protecting old-growth ecosystems for biodiversity resilience. By linking TreM patterns to forest structure and environmental gradients, this study establishes a foundation for evidence-based management strategies in temperate forests worldwide.